MRI features of the placenta in fetuses with and without CNS abnormalities. Issue 9 (September 2018) - Shapira-Zaltsberg, G.; Grynspan, D.; Quintana, M.V.; Dominguez, P.C.; Reddy, D.; Davila, J.H.; Miller, E.
Abstract : Aim: To investigate if magnetic resonance imaging (MRI) features of the placenta are different in fetuses with and without central nervous system (CNS) abnormalities. Material and methods: Institutional research ethics board approval was obtained. Fetal MRI of 97 singleton pregnancies were analysed retrospectively (19–25 weeks gestation), 65 with CNS morphological abnormalities and 32 controls. Placental T2 signal intensity, placental and fetal volumes, placental-to-fetal volume ratio, and placental apparent diffusion coefficient (ADC) values were assessed. Measurements were compared with the presence or absence of CNS fetal abnormalities using the Mann–Whitney test. Separate slopes models and intercept models were used to check for significant differences in the slopes and intercepts, respectively, among the groups. Results: Placental ADC values were significantly lower in placentas of fetuses with CNS abnormalities compared to controls ( p= 0.04). Placental T2 signal intensity, fetal and placental volumes did not differ between the two groups. The rate of increase in fetal-to-placental volume ratio with gestational age (GA) was greater among the controls. Conclusion: The presence of fetal CNS abnormalities is associated with reduced ADC values of the placenta. Moreover, placentas of fetuses with CNS abnormalities show a less rapid increase in fetal to placental volume ratio with GA. Therefore, ADC mapping, as well as different growth kinetics of the placenta relative to the fetus, may potentially serve as early markers of pathological neurodevelopment. Highlights: Placental characteristics of fetuses with and without CNS anomalies were compared. The presence of fetal CNS anomalies is associated with reduced placental ADC values. CNS anomalies are associated with slower increase in fetoplacental volume ratio.